Creative Arabic Learning Based On Quizizz: Model And Impact - Qurrotul A'yuni; Danial Hilmi; Salma Laksmita Benedik; Bakri Mohamed Bkheet Ahmed (Institut Agama Islam Negeri (IAIN) Metro, 2022)
Since entering the Covid pandemic, learning has been shifted simultaneously to an online or blended learning mode. Teachers need alternative creative learning based on media and digital- guides, including Arabic language teachers. The article aims to describe the creative learning model using Quizizz and its impact. For this reason, descriptive qualitative type of field study is used as research method. The results are; 1) After the teacher is able to design a creative Arabic learning model from planning, implementation, and assessment, it shows that the teacher can analyze students needs, able to be creative, active, and fun, and also the teacher has good professionalism; 2) Quizizz has a positive impact on students and their grades and learning performance.